Study of Cardiovascular Risk Assessment in Patients with Fatty Liver Disease (Indian Journal of Public Health Research & Development, 2020)
Background- The term ‘fatty liver disease’ (FLD) is used to describe a variety of liver diseases of differentseverity, from pure steatosis to steatohepatitis and cirrhosis and hepatocellular carcinoma. ObjectiveTo Study Of Cardiovascular Risk Assessment In Patients With Fatty Liver Disease. Methodology- Thisprospective single center study was conducted from 1st March 2015 to 1st March 2016, in the Department ofGastroenterology in collaboration with Department of Community medicine at Global hospitals. All Adult(18 years to 70 years) patients, both sexes, reporting to Medical Gastroenterology with FLD were includedin the study which were 32.Result - Maximum 28 subjects (87.5 %) were male while 4(12.5%) were female.Male to female ratio was 7:1. Maximum patients 20(62.5%) belonged to Grade II fatty liver followed by09 (28.12%) Grade I and 03(9.3%) Grade III. 11(34.37%) were overweight,17 (53.12%) were obese,only 4patients had normal BMI. 27(96.42%) out of 28 male patients had abnormal waist while four (100%) out of4 female patients had abnormal waist circumference. 12(37.50) Patients with FLD had significantly higherlevels of total cholesterol.Conclusion- . FLD may serve as a trigger for assessment of cardiovascular riskfactors, and such patients should undergo further cardiovascular assessment.
Keywords: Cardiovascular risk assessment; fatty liver disease.